(untitled) (Indian Journal of Public Health Research & Development, 2021)
Aim: The aim of this study is to develop and validate the Non-verbal Social Skill Rating Scale for Mentally Ill. Objectives: • To generate the scale items through focus group discussion. • To identify the appropriateness and relevance of items through subject matter expert rating. • To establish the psychometric properties of developed scale. • To develop norms for developed scale. Methodology: Formulation of 48 statements was done with focus group discussion. The statements were sent to 26 experts in the field of Occupational therapy, Psychiatrist Psychologist and Psychiatric Social Worker for validating the items. Total of 48 items are validated by the experts. A total of 100 samples including Bipolar disorder, Schizophrenia, Depression, Anxiety, Schizoaffective disorder and acute psychosis were selected for the field trial or main study those who were residing in psychiatric homes at Tamil Nadu. Samples were selected by using convenient sampling method. Socio demographic data sheet prepared by investigators were used for collecting baseline information. Conclusion: This research shows the assessment tool has good internal consistency and reliability. The expert validation was done and got good relevance. Hence, Non-verbal Social Skill Rating Scale for Mentally Ill indicated that the scale is a reliable and valid measure of Non-verbal social skills, which is used to identify the level of Non-verbal Social Skill of Mentally Ill.